EFFECT OF WATER REGIMES AND ORGANIC ACIDS ON Mg- INTERLAYERING FORMATION IN EXPANSIBLE 2:1 MINERALS IN SOME SOILS OF KURDISTAN REGION, IRAQ - A . H. Goran,; S. K. Essa, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the occurrence of chloritization phenomenon in these soils. Three of these pedons were chosen in soil sites differing in their agricultural exploitation, which included: one pedon in an uncultivated soil at Daratw . While the second pedon was dug in soil exploited by the cultivation of  wheat at Bardarash . The third pedon was chosen as representative of a forest soil at Tawska Valley. Also, another two soil pedons were exposed to successive cycles of wet and dry, were chosen in Aski Kalak , and  Altun Kupri districts. All studied soils were examined by X-ray diffractions. Results showed the presence of Mica, Smectite, Real chlorite and Kaolinite minerals in clay fraction of these soils.  Results also, showed the precipitation of Brucite layer into Montmorillonite interlayers and caused to shifting Montmorillonite towards Chlorite mineral in Aski Kalak , Altun Kupri, and forest soil pedons, this was attributed to creation a suitable conditions to encouraged a chloritization phenomenon to occur in these soils.